Multiracialism in Singapore : community centers as a mediating structure for racial harmony. - Tan, Jeannie Yujuan. (2011)
This paper problematizes the idea of multiracialism in Singapore. While many would agree that Singapore is a multiracial nation-state, little has been done to illustrate the extent to which this is so. Instead of treating it as a taken-for-granted concept to be managed and lived with, this paper seeks to question its very existence. Using the Community Center as a site of study, the paper will illustrate how much multiracialism is actively sought after by the state, but is not always as enthusiastically taken up or given meaning by residents. Community Centers, I suggest, become merely another site for citizens to pursue their individual needs and multiracialism in Singapore remains in its nascent stage of development. I also suggest that tolerance among the racial groups, although regarded by both the state and citizens as an ideal, breeds passivity at best and apathy at worst, inhibiting the kind of active citizenry that is essential for any genuine form of racial harmony. Although with limitations, findings in this case study will be a useful addition to the existing scholarship on multiracialism in Singapore and its inevitable repercussion on an overarching national identity. Providing an analysis of some of the factors that affect residents’ commitment to community development, namely, self-interest, the tendency to retain their ethno-racial identities and structural constraints, findings will also, hopefully, inform future policies in Singapore, especially those pertaining to interactions among residents.